Penyelesaian Persamaan Telegraph Dan Simulasinya - Surur, Agus Miftakus; Adi, Yudi Ari; Sugiyanto, Mr. (Jurnal Fourier, 2013)
Equation Telegraph is one of type from wave equation. Solving of the wave equation obtainable by using Greens function with the method of boundary condition problem. This research aim to to show the process obtain;get the mathematical formula from wave equation and also know the form of solution of wave equation by using Greens function. Result of analysis indicate that the process get the mathematical formula from wave equation from applicable Greens function in equation which deal with the wave equation, that is applied in equation Telegraph.Â  Solution started with searching public form from Greens function, hereinafter look for the solving of wave equation in Greens function. Application from the wave equation used to look for the solving of equation Telegraph.Â  Result from equation Telegraph which have been obtained will be shown in the form of picture (knowable to simulasi) so that form of the the equation Telegraph.